1997
DOI: 10.3758/bf03210805
|View full text |Cite
|
Sign up to set email alerts
|

Computational and reasoning abilities in arithmetic: Cross-generational change in China and the United States

Abstract: A Chinese advantage over Americans was found for economically relevant computational and reasoning abilities in arithmetic for groups of 6th-and 12th-grade students matched or equated on general intelligence. No cross-national difference for computational or reasoning abilities was found for samples of older (60-to 80-year-old)Chinese and American adults equated on general intelligence. The pattern of change in arithmetical competencies across cohorts suggests that the Chinese advantage in 6th and 12th grade i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 10 publications
4
31
2
Order By: Relevance
“…Consistent with this pattern is the finding of comparable performance of younger and older American adults, and sometimes an advantage for older adults, on tests of computational arithmetic (Geary, Salthouse, et al 1996). In contrast, younger adults in mainland China consistently outperform their older peers on the same tests (Geary et al, 1997;Geary, Salthouse, et al, 1996). The overall pattern suggests that older American adults have had considerably more experience with computational arithmetic than younger American adults and that if they were equated on experience, then younger adults would outperform older adults on arithmetic tests in the United States, as in China.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Consistent with this pattern is the finding of comparable performance of younger and older American adults, and sometimes an advantage for older adults, on tests of computational arithmetic (Geary, Salthouse, et al 1996). In contrast, younger adults in mainland China consistently outperform their older peers on the same tests (Geary et al, 1997;Geary, Salthouse, et al, 1996). The overall pattern suggests that older American adults have had considerably more experience with computational arithmetic than younger American adults and that if they were equated on experience, then younger adults would outperform older adults on arithmetic tests in the United States, as in China.…”
mentioning
confidence: 63%
“…Conceptually, the goal was to do so in a way that tested our hypothesis that these cognitive arithmetic ndings are due to a schooling-related cross-generational decline in arithmetical competencies in the United States (Geary et al, 1997).…”
Section: Hypothesismentioning
confidence: 99%
“…Several studies found differences between East Asians' and North Americans' performance on simple arithmetic (see, e.g., Campbell & Xue, 2001;Chen & Uttal, 1988;Geary, 1996;Geary, BowThomas, Liu, & Siegler, 1996;Geary et al, 1997;Geary, Liu, & Bow-Thomas, 1992;Geary, Salthouse, Chen, & Liu, 1996;LeFevre & Liu, 1997;Penner-Wilger, LethSteensen, & LeFevre, 2002;Stevenson, Chen, & Lee, 1993;Stevenson et al, 1990;Stevenson, Lee, & Stigler, 1986). Because East Asians rely primarily on memory retrieval, their arithmetic performance is faster and less error prone than that of North Americans, who frequently use procedures.…”
Section: Individual Differencesmentioning
confidence: 99%
“…Other quite surprising results have been found concerning the arithmetic abilities of normal educated adults. Geary, Salthouse, Chen, and Fan (1996) and Geary et al (1997) showed declines in mental arithmetic performance across successive North-American generations. Comparable results were obtained by Mulhern and Wylie (2004), who showed that performance levels of…”
mentioning
confidence: 99%